If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7.2 = 6y Solving -7.2 = 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. -7.2 + -6y = 6y + -6y Combine like terms: 6y + -6y = 0 -7.2 + -6y = 0 Add '7.2' to each side of the equation. -7.2 + 7.2 + -6y = 0 + 7.2 Combine like terms: -7.2 + 7.2 = 0.0 0.0 + -6y = 0 + 7.2 -6y = 0 + 7.2 Combine like terms: 0 + 7.2 = 7.2 -6y = 7.2 Divide each side by '-6'. y = -1.2 Simplifying y = -1.2
| 2x-2+8x-4=5x+8-x+4 | | 2/5(2x+13)=4(3-2x)+2 | | 4d-2=3-11d | | x^2+y^2+4x-8y+16=0 | | n^2+7=8n | | 3x+131/11=10 | | -2+k/6=10 | | x^2+y^2-4x-1=0 | | 7m^2-18m+8=0 | | 6x+11=3x+98 | | 7a+3=-53 | | xy+2y-6=0 | | 3r+14=7 | | 4-2(x+3)=13-5(x+4) | | -3(4x-9)+5=-12x+32 | | 10x+6=3(3x-1)+9 | | -2x+10+4x/2=4 | | -9x-21=-61 | | (x+4)^2-20/4 | | 3/4x+2x=22 | | 1/15x+1/5x=2/3x | | 2(2m-3n)-8n= | | 2/3x-7=-3 | | 9(x+4)-6=32-3x-2+12x | | 1/4+x=-7/4 | | 5.4/2.4=x/1.6 | | 7(6+-2a)=(-3a+1) | | -6+6(x-2)=14x+4-8x | | x=p/c+d | | 3-7*5+2*4= | | A+8=300+8 | | x=5x-6 |